2009
DOI: 10.1007/s00726-009-0338-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biosynthesis of an Ala-scan library based on the cyclic peptide SFTI-1

Abstract: We present the in-vivo biosynthesis of wild-type sunflower trypsin inhibitor 1 (SFTI-1) inside E. coli cells using an intramolecular native chemical ligation in combination with a modified protein splicing unit. SFTI-1 is a small backbone cyclized polypeptide with a single disulfide bridge. A small library containing multiple Ala mutants was also biosynthesized and its activity was assayed using a trypsin-binding assay. This study clearly demonstrates the exciting possibility of generating large cyclic peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 39 publications
0
83
0
3
Order By: Relevance
“…Эти подходы подробно рассмотрены в ряде обзоров [43,85,93]. Первый подход был использован для получения гетерологической экспрессией в E. coli SFTI 1 и библиотеки его аналогов для аланинового скрининга [94]. В работе [95] [95].…”
Section: метод гетерологической экспрессииunclassified
“…Эти подходы подробно рассмотрены в ряде обзоров [43,85,93]. Первый подход был использован для получения гетерологической экспрессией в E. coli SFTI 1 и библиотеки его аналогов для аланинового скрининга [94]. В работе [95] [95].…”
Section: метод гетерологической экспрессииunclassified
“…These requirements usually depend on the type of split-intein used, and seriously limit the diversity of the libraries that can be generated when using small cyclic peptide templates. Our group has recently demonstrated the expression in E. coli of libraries based on the cyclic peptide SFTI-1 (a backbone cyclized Bowman-Birk trypsin inhibitor) using an intein-mediated backbone cyclization approach (see above), which allows the biosynthesis of backbone-cyclized polypeptides without any sequence requirement limitation [89].…”
Section: Screening Of Cyclotide-based Librariesmentioning
confidence: 99%
“…This library was cyclized in vitro by incubation with a redox buffer containing reduced glutathione (GSH) as a thiol co-factor, thus mimicking the intracellular conditions, where GSH is the most abundant thiol co-factor. The use of GSH allows the cyclization and folding to happen in one step [69,89]. Analysis of the cyclization/folding reaction by HPLC and mass spectrometry revealed that all the members of the kalata B1 based library were expressed and processed with similar yields to give the corresponding natively folded cyclotides [69].…”
Section: Screening Of Cyclotide-based Librariesmentioning
confidence: 99%
“…A wide range of chemical [54][55][56] and biological [57][58][59][60] studies on the synthesis of cyclotides have been carried out recently and these typically involve the formation of a head-to-tail cyclic backbone before disulfide bond formation, rather than the reverse, as is thought to occur in nature, that is, disulfide bond formation followed by cyclization via the AEP as described above. The closest mimic to the natural biosynthesis is perhaps a chemoenzymatic approach in which a linearized version of MCoTI-2 was chemically synthesized and then enzymatically cyclized using trypsin [61 ].…”
Section: Current Opinion In Chemical Biologymentioning
confidence: 99%
“…The relationship between the in vitro efficacy and the in vivo efficacy of antimicrobial agents remains unclear, and prediction of in vivo activity is very challenging, due to variations in potency that can occur due to many uncontrolled parameters in the host systems (58,59). Despite the challenges of using in vitro potency to predict in vivo potency, we found that the most potent peptide in the in vitro study, pYR, was also the most potent peptide in treating S. aureus skin infections in mice.…”
Section: Fig 4 Cytotoxic Activity Of Selected Orb and Pyr Peptides Agmentioning
confidence: 99%